Determination of fast gas–liquid reaction kinetics in flow. Issue 1 (21st November 2019) - Zhang, Jisong; Teixeira, Andrew R.; Zhang, Haomiao; Jensen, Klavs F.
Abstract : A flow concept is developed to measure fast gas–liquid reaction kinetics based on a tube-in-tube reactor. Abstract : We present a flow concept to measure fast gas–liquid reaction kinetics. A tube-in-tube reactor design with semipermeable Teflon AF-2400 tubes is adopted to achieve fast gas–liquid mass transfer without direct contact of gas and liquid. By performing a steady-state flux balance of both gas and liquid flowing into the reactor and developing a mathematical model based on the film theory, the reaction kinetic parameters can be determined with excellent precision with the use of only a single gas flow meter. Reactions of CO2 with alkanolamines and ozonolysis of organics serve as case studies to assess the ability of the technique to resolve reaction kinetics in situ . The proposed strategy presents a new opportunity for the study of fundamental aspects of gas–liquid reactions in a simple, safe, automated and high-throughput manner.